QUO VADIS PERLINDUNGAN HUKUM TERHADAP KORBAN MELALUI RESTITUSI (Perspektif Filsafat, Teori, Norma dan Praktek Penerapannya) - Suhariyanto, Budi (Jurnal Hukum dan Peradilan, 2013)
Restitution is a form of legal protection form for victims of victim recovery oriented. Normatively, on the positive law, restitution has not been cooperated well yet. Consequenly, the application of the restitution had a problem, specifically unsynchronized legal structure. Under the integrated criminal justice system perspective, legal structure and legal substance disharmony need to be reorganized (regulated). A fundamental arrangement will be done by rephylosophy some punishment, than make restitution become a prinsipal (main)criminal and giving a new position for the victim to the later integrated criminal justice system based on the phylosophy of restoratifjustice. Keywords: legal protection, victims, restitution.